2010
DOI: 10.1007/s11666-010-9551-7
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Tribological Performance of Nanostructured ZrO2-3 mol% Y2O3 Coatings Deposited by Air Plasma Spraying

Abstract: In this study, nanostructured ZrO 2 -3 mol% Y 2 O 3 coatings were deposited by air plasma spray using reconstituted feedstock. The coating structures were characterized by x-ray diffractometer, micro-Raman spectrometer, field emission scanning electron microscope, and transmission electron microscope. It is revealed that the as-sprayed coating is mainly composed of columnar grains with diameters <100 nm and demonstrates the better toughness, higher microhardness, and lower porosity. It consists only of nontran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Choi et al [38] showed that H for APS 8 YSZ coatings increases from the as-received value of 2.34-4.49 GPa when the thermal aging time equals about 5 h. Then, it gradually approaches a plateau of 4.36 GPa after annealing 500 h [3]. The results in this paper are in agreement with these data, but they are less than that of nano-structured APS YSZ coatings [40]. Similarly, using the given H, E and Eq.…”
Section: Evaluation Of K Ic By Vickers Indentationsupporting
confidence: 89%
“…Choi et al [38] showed that H for APS 8 YSZ coatings increases from the as-received value of 2.34-4.49 GPa when the thermal aging time equals about 5 h. Then, it gradually approaches a plateau of 4.36 GPa after annealing 500 h [3]. The results in this paper are in agreement with these data, but they are less than that of nano-structured APS YSZ coatings [40]. Similarly, using the given H, E and Eq.…”
Section: Evaluation Of K Ic By Vickers Indentationsupporting
confidence: 89%
“…Similar findings related to improved wear resistance compared to conventional coatings was reported by Liang et al in the case of nanostructured coatings, and the reason was attributed to their enhanced mechanical properties (higher hardness, higher cohesive strength, higher toughness, etc.) [23]. The above results from our preliminary study with carbide suspensions show considerable promise and clearly motivate further, more detailed, investigations.…”
Section: Resultssupporting
confidence: 57%
“…Some example of nanostructured ceramic coatings obtained by APS from agglomerated powders include alumina [16,17], titania [18,19], alumina-titania [14,20], yttria-stabilised zirconia [21,22] or pyrochlore [23].…”
Section: Introductionmentioning
confidence: 99%